Native-Speakerism Ideology Among EFL Students in English Language Learning and Teaching: A Survey Study - Adalta, Febri Aini; Arsyad, Safnil (UNIB Press, 2023)
Native speakerism is an ideology in which people believe that real and correct English comes from the people who were born in Europe and use English as their mother tongue. This point of view may have an impact on